2018
DOI: 10.1021/acs.jpcb.8b08911
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Cations in Aqueous Solutions of Multiheaded Cationic Surfactants: All Atom Molecular Dynamics Simulation Studies

Abstract: Self-assembly of multiheaded surfactants in aqueous solutions has been investigated using atomistic molecular dynamics simulations. The model multiheaded surfactants contain multiple head groups ranging from one to four for a single tail group. Increase in the number of charged head groups has substantial consequences in the aggregation properties of surfactants in their aqueous solutions. Polydisperse aggregates of surfactants are formed in the aqueous solution. The shape and size of the aggregates are dictat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…Much work has been done to understand the properties of surfactant aggregates in solutions, but systematic studies of adsorption kinetics and the structure of the adsorbed layer at the interface are still not sufficient . A large number of experimental studies have been performed on the properties of surfactant adsorption layers at vapor/liquid, liquid/liquid, and liquid/solid interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Much work has been done to understand the properties of surfactant aggregates in solutions, but systematic studies of adsorption kinetics and the structure of the adsorbed layer at the interface are still not sufficient . A large number of experimental studies have been performed on the properties of surfactant adsorption layers at vapor/liquid, liquid/liquid, and liquid/solid interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that the clusters formed by cooperative hydrogen bonding interactions could further influence the phase behavior of ILs at a low temperature. Sharma and Bhargava studied the aggregation behavior of multiheaded surface-active ILs in water and found that the shape and size of aggregates were directly related to the number of charged head group of cations . Nadimi et al studied the aggregation behavior of two kinds of amino acid ILs in aqueous, they found that both of them can aggregate quasi spherical clusters, and hydrogen bonding was the fundamental reason for their aggregation …”
Section: Introductionmentioning
confidence: 99%
“…Sharma and Bhargava studied the aggregation behavior of multiheaded surface-active ILs in water and found that the shape and size of aggregates were directly related to the number of charged head group of cations. 46 Nadimi et al studied the aggregation behavior of two kinds of amino acid ILs in aqueous, they found that both of them can aggregate quasi spherical clusters, and hydrogen bonding was the fundamental reason for their aggregation. 47 Furthermore, many simulations for the self-aggregation of ILs in aqueous were performed.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it was found that the solubilization of rebamipide was more favorable between Stevia-G and C 16 TAC, as was measured through the molar solubilization ratio (MSR) and partition coefficient ( K m ) estimation . In terms of theoretical perspective, on the basis of the simulation study, Sharma et al have estimated the self-assembly of multiheaded surfactants in aqueous solutions . It was found that the increase in the number of charged head groups affects the aggregation propensity of surfactants in their aqueous solutions.…”
mentioning
confidence: 99%
“…2 In terms of theoretical perspective, on the basis of the simulation study, Sharma et al have estimated the self-assembly of multiheaded surfactants in aqueous solutions. 3 It was found that the increase in the number of charged head groups affects the aggregation propensity of surfactants in their aqueous solutions. Specifically, this simulation study indicates that, with an increase in the number of charged head groups on the surfactants, the aggregation number decreases.…”
mentioning
confidence: 99%